Male partners’ support and influence on pregnant women’s oral PrEP use and adherence in Malawi - Young, Alinda M.; Saidi, Friday; Phanga, Twambilile; Tseka, Jennifer; Bula, Agatha; Mmodzi, Pearson; Pearce, Lisa D.; Maman, Suzanne; Golin, Carol E.; Mutale, Wilbroad; Chi, Benjamin H.; Hill, Lauren M. (Frontiers in Reproductive Health, 2023)
Introduction Daily oral pre-exposure prophylaxis (PrEP) is a safe and effective HIV prevention method for pregnant and postpartum women, but adherence barriers exist. Understanding the role of male partners in supporting PrEP use may inform strategies to support PrEP adherence among pregnant and breastfeeding women. Methods To understand male partners’ involvement in women's use of PrEP, we conducted in-depth interviews with pregnant women in Lilongwe, Malawi who had recently decided to use PrEP (n = 30) and their male partners (n = 20) in the context of a PrEP adherence trial. Women were purposively recruited to ensure variation in their partners’ HIV status. Interviews were conducted in Chichewa using a semistructured guide. We followed a thematic approach to analyze the interview data. Results Most male partners were receptive to women using PrEP during pregnancy because it eased their fears of the woman and baby acquiring HIV. Men often played a key role in women's PrEP adherence by providing daily reminders and encouragement to adhere to their medication. The majority of women appreciated this support from the men as it lessened the burden of remembering to take their medications daily on their own and aided their adherence. However, several women who lacked male partner support spoke of wanting their partners to be more involved. Many men living with HIV found the mutual support beneficial for their antiretroviral therapy adherence, while men without HIV or with status unknown appreciated knowing that the family was protected. While most men were open to women continuing PrEP beyond the current study, some would only support it if women were still at risk for acquiring HIV. Conclusion In this study, male partners were strongly motivated to support the PrEP adherence of their female partners as a way of ensuring that the pregnant women and unborn babies were protected against HIV. Promoting disclosure and tangible support that arises organically among men may be helpful, but programs to enhance this support and identify ways to support women who do not receive support from their partners or do not wish to disclose their PrEP use to partners may be needed.